Electrochemical Behaviour of Nanoscale Ni Modified Screen-Printed Carbon Electrodes in Corrosion Tests and Hydrogen Evolution Electrocatalysis - Škantárová, Lenka; Oriňáková, Renáta; Straková Fedorková, Andrea; Bača, Petr; Sedlaříková, Marie; Oriňák, Andrej (ESG, 2015)
Corrosion resistence and electrocatalytic aktivity were examined for Ni nanoparticles ( NiNPs) coated screen printed carbon based electrodes ( SPCEs) being a novel alternative to unmodified electrodes. Corrosion as well as hydrogen evolution reaction (HER) measurements were performed in 1 mol/L H2SO4 using potentiodynamic polarization method, moreover electrochemical impedance spectroscopy (EIS) measurements were carried out

Corrosion resistence and electrocatalytic aktivity were examined for Ni nanoparticles ( NiNPs) coated screen printed carbon based electrodes ( SPCEs) being a novel alternative to unmodified electrodes. Corrosion as well as hydrogen evolution reaction (HER) measurements were performed in 1 mol/L H2SO4 using potentiodynamic polarization method, moreover electrochemical impedance spectroscopy (EIS) measurements were carried out
Electrochemical Behaviour of Nanoscale Ni Modified Screen-Printed Carbon Electrodes in Corrosion Tests and Hydrogen Evolution Electrocatalysis
Keywords: Carbon based electrodes; acid corrosion; electrodeposited films; screen printed electrodes; Carbon based electrodes; acid corrosion; electrodeposited films; screen printed electrodes